2017
DOI: 10.1039/c7ra09042k
|View full text |Cite
|
Sign up to set email alerts
|

MiR-138-5p targeting LIMK1 suppresses breast cancer cell proliferation and motility

Abstract: Breast cancer is the most frequently diagnosed female cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The expression of LIMK was elevated in many kinds of tumours, especially highly invasive malignancies. LIMK 1 plays an important role in the invasion and metastases of tumours by regulating the actin cytoskeleton molecules . Recently, the significance of LIMK1 in tumorigenesis has aroused extensive concern .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of LIMK was elevated in many kinds of tumours, especially highly invasive malignancies. LIMK 1 plays an important role in the invasion and metastases of tumours by regulating the actin cytoskeleton molecules . Recently, the significance of LIMK1 in tumorigenesis has aroused extensive concern .…”
Section: Discussionmentioning
confidence: 99%
“…Inactivated cofilin lost the ability of binding to actin filaments which improved the stability of F‐actin, resulting in the change of actin cytoskeleton . Several studies have now confirmed that the expression of LIMK1 is consistently elevated in the many kinds of tumours including breast cancer, ovarian cancer, colon cancer and gastric cancer . However, researchers have paid little attention to the role of LIMK1 in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal movement ability by performing scratch wound healing assay and vertical movement ability by performing transwell migration and invasion assay was performed as described previously [ 35 ]. Gelatin zymography was performed as described previously [ 36 ] to analyze MMP-9 and MMP-2 activity using CM derived from miR-140-5p-KD or miR-140-5p-OE cells.…”
Section: Methodsmentioning
confidence: 99%
“…10 Li et al showed that miR-138 posttranscriptionally regulated LIMK1 to suppress the proliferation of breast cancer cells. 11 These studies have revealed an important tumor suppress function of miR-138 in various cancers. Moreover, miR-138 has been demonstrated to function as a tumor suppressor in glioblastoma (GBM) via regulating EZH2/CDK4/6-E2F1 signal loop.…”
Section: Introductionmentioning
confidence: 99%